Isolation and Identification of β-sitosterol, 7-hydroxystigmast-22-en-3,6-dione and 3β, 24(S)-dihydroxycholesta-5, 25-diene-7-one from stem bark of Nauclea pobeguinii - Adewusi John Adepoju; Sunday Olusegun Oladoye; Ezekiel Temidayo Ayodele; Adeola Victoria Falade; Gin Keat Lim; Chuan Wei OO (Majalah Obat Tradisional, 2022)
The stem bark of the Nauclea pobeguinii was collected, air-dried, and pulverized and was extracted with solvent of varying polarity (n-hexane, ethyl acetate, and ethanol) to obtain the crude extracts. Silica gel column and thin layer chromatographic separation afforded three compounds whose structures were elucidated as β-sitosterol (1), 7-hydroxystigmast-22-en-3.6-dione (2), and 3β, 24(S)-dihydroxycholesta-5, 25-dien-7-one (3) by analysis of their chemical and spectral characteristic from 1D and 2DNMR, FTIR and by comparing of data with those reported in the literature.